Castiglione della Pescaia (Grosseto), Italien. Auf der Suche nach den Häfen der etruskischen Stadt Vetulonia. Die Arbeiten der Jahre 2016 bis 2018 - Colombi, Camilla (e-Forschungsberichte des DAI, 2018)
The Etruscan settlement of Vetulonia was an important trading centre, located on the top of a small hill from which it overlooked the former marine bay of the “Prile lake”. It can be assumed that the city had harbours or piers on the lake, where raw materials, as well as local and exotic products, were traded. However, the connection of the Etruscan town to the bay and the location of its harbours are still unknown and never were the subject of an archaeological investigation. In 2016 the Rome Department of the DAI started an interdisciplinary research project with the goal to locate and explore the potential harbours, as well as to contribute to the reconstruction of the original extension of the bay and its subsequent silting up.